On the identity of Trichogramma demoraesi Nagaraja (Hymenoptera: Trichogrammatidae), with a checklist and a key to Trichogramma species associated with Erinnyis ello (L.) (Lepidoptera, Sphingidae) in Brazil - Vieira, Jaci M.; Querino, Ranyse B.; Zucchi, Roberto A. (Zootaxa, 2014)
Specimens collected from eggs of the cassava hornworm Erinnyis ello, originally identified as T. demoraesi, were compared with the paratype of this species. Based on morphological analysis, the specimens from E. ello actually belong to Trichogramma marandobai Brun, Moraes and Soares, 1986. Therefore, T. demoraesi is not a parasitoid of the eggs of E. ello, a major pest of cassava. The main features separating the two species, and a checklist and key to the species of Trichogramma associated with E. ello are presented.